FACTORS AFFECTING THE ADOOTION OF SELECTED BRANDS OF RICE IN AN-NAJAF ALASHRAF PRONINCE FOR THE AGRICULTURAL SEASON 2017 - & et al., kery (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was implemented on rice farmers in An-Najaf Alshraf Province. It aims at economic assess of rice brands  Jasmine – Anbar 33 – Anbar Albaraka .on random layer sample with ratio of  5% . The research depend, to achieving its targets, on using Cost-Benefit Analysis CBA and ADOPT  program to assess these brands and identify how far farmers will be familiar to the best brand. Many conclusions have been achieved. The most important ones maybe: the net retuen which is  331  thousands Dinar/ dunums in case of cultivating the brand. This is higher than the net benefit in case of cultivating jasmine brand which is  289   thousand Dinars/ dunums.  The interned rate of return was  1.23 . The standard ratio of benefit to the cost is  1.63% . and this refers that the Dinar invested in cultivating Anbar Albaraka brand will benefit with amount equal to  1.63  Dinar. Results also showed that it is expected to adopt brand of  52%  of farmers during a duration of  14.9  years. The programs of  ADOPT  program have showed that it is expected there will be adaptation for the technology from  52%  of farmers within a time duration may be about  14.9 . The sensitivity analysis indicated that there could be decrease or increase in this duration by effecting on number of factors such as  short term financial restrictions-simple experimental of brand on limited scale- the degree of technical complexity- average awareness and cognition for farmers in using the brand – finally, the first investment to the annual benefit. So, according to the results, the adaptation of Anbar Albaraka will contribute, when cultivated on a large scale,  in  improving the standard  of living  of farmers and achieving part of developing targets in the agriculture sector.